Routine computerized tomography scanning, groin ultrasound with or without fine needle aspiration cytology in the surgical management of primary squamous cell carcinoma of the vulva. Issue 1 (1st January 2006) - Land, R.; Herod, J.; Moskovic, E.; King, M.; Sohaib, S. A.; Trott, P.; Nasiri, N.; Shepherd, J. H.; Bridges, J. E.; Ind, T. E.J.; Blake, P.; Barton, D. P.J.
Abstract : We set out to study whether computerized tomography (CT) scanning of the vulva and the groin and groin ultrasound scanning (USS) alone or with fine needle aspiration cytology (FNAC) (USS/FNAC) influenced or could influence the surgical management of primary squamous cell carcinoma of the vulva (SCCaV). Forty-four patients underwent surgery for primary SCCaV following radiologic imaging by one or more modalities. Patient details included the clinical assessment of the carcinoma, radiologic findings, the operation performed, and whether the decision regarding the type and extent of surgery for the vulval carcinoma and, in particular, for the groin node dissection was or could be influenced by the radiologic findings. The age range was 38–87 years, with a median of 74 years. A total of 75 groin dissections were performed. Twenty-five of the 44 patients (56.8%) did not have groin node metastasis, 14 had unilateral metastasis (31.8%), and 5 (11.4%) had bilateral metastasis. All cases with histologically proven nodal status were analyzed to compare the preoperative imaging status with the histology. The calculated sensitivity, specificity, negative predictive value, and positive predictive value for CT were 58%, 75%, 75%, and 58%, for USS alone—87%, 69%, 94%, and 48%, and for USS-guided FNAC—80%, 100%, 93%, and 100%, respectively. There was no patient in whom surgical planning for the vulval carcinoma or the groin nodes was or could be altered by the CT findings. The data do not support the routine use of CT scanning in patients with primary SCCaV, either in assessment of the primary vulval carcinoma or in detecting groin nodal metastases. For the groin nodes, USS/FNAC is superior to CT in assessing disease status. In contrast to CT, USS/FNAC may have a useful clinical role in the management of the groin nodes in vulval carcinoma.